Practical lubrication for industrial facilities - Bloch, Heinz P. (Fairmont Press Marcel Dekker, 2000)
"This text provides an important reference which will enable the reliability professional, mechanic, machinist, or lubrication specialist to understand what matters most in a lubricant, and to distinguish mere sales talk from relevant facts. The information provided in this book is intended to assist the professional in insuring that machinery operates at optimum performance levels, with a minimum of costly downtime."--BOOK JACKET.